A Critical Analysis of Teaching Language Learning Strategies to University in Indonesia - M. Ainur Rizqi; Haries Pribady (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2017)
Over the last 40 years, plenty research has extensively examined the role of learning strategies on the language acquisition/learning. In Indonesia, unfortunately, this issue seemingly receives less attention at least until 2000’s.  Perhaps, Setiyadi’s (2001; 2004) and Mistar’s (2001) work which both studied students’ learning strategies in a university degree could be declared as the first batch of strategies-oriented research, and followed by  Subekti& Lawson (2007) and Mistar&Umamah (2014). Generally, the studies were descriptive or correlational in which depicting the types of strategies that the learners employed, or sought a relationship between learning strategies and the learners’ academic achievements. Strikingly, none elucidated strategy-instruction as the key priority. In fact, this is vital to ensure whether these strategies really could help poor language learners in practice.